The right of Access to higher education: the case of Vietnam - Vu, Cong Hao (Đại học Quốc gia Hà Nội, 2020)
The Education System of Vietnam: An Overview. Situation and adopted policies which promote the the right of access to higher education in Vietnam. National framework or mechanism on the promotion and protection of the right of access to higher education in Vietnam. Promotion and protection of the right of access to higher education in Vietnam: Opportunities and Challenges. Conclusion